The Destination Marketing Development of Religious Tourism in Uzbekistan - Navruz-Zoda, Bakhtiyor (The international journal of religious tourism and pilgrimage, 2016)
Uzbekistan has great potential to develop pilgrimage tourism based on the spiritual culture of the Islamic religion. Destination marketing development of religious tourism, based on Sufism is an innovative direction for the organisation of pilgrimage tourism. In this paper, the dual nature of this kind of religious tourism is revealed to comprise: first a pilgrimage nature, that consists of the Sufi pilgrimage to Sufi shrines to perform ritual and; secondly a religious-cognitive nature, whereby, a major segment of travellers can be Muslim, non-Sufis and scientists, researchers, teachers, tutors and other categories of tourists who are interested in the learning of Sufism. For the stable development of inbound international religious tourism, we have applied a destination marketing methodology, based on a combination of the marketing concept and theory of regional management. In the paper, applying the concept of destination marketing to religious tourism along with the traditional concept of holy places', the religious destination' concept is introduced along with the creation of a new, Sufipilgrimage and religious-cognitive destination - The Homeland of Sufi Sultan - Bahaud-Din Naqshband' (acronym: SP&RCD Sufi Hajj'). The marketing tools for this destination are being developed. Depending on the purpose of travel to Sufi shrines, a tailored version of the tour program is recommended. In addition, market segmentation of the SP&RCD Sufi Hajj' is implemented according to travel purposes, conviction, geographical basis and gender. In the report, the organisational structure of a new intermediary-marketing company Sufipilgrimdestination, which is designed to control the flow of foreign pilgrims to Uzbekistan, is substantiated. As a brand for this destination, an image is selected, which includes a picture of the Baha-ud-Din Naqshband Ensemble in the centre (this site is located in the suburb of Bukhara); with the inscription: Travel to the Holy Bukhara - Motherland of Sufi Sultan Baha-ud-Din Naqshband'.